Retrotransposon insertion into the maize waxy gene results in tissue-specific RNA processing. - Marillonnet, S (1997)
We previously reported that three alleles of the maize waxy (wx) gene were alternatively spliced as a result of the insertion of retrotransposons into intronic sequences. In addition, inefficient splicing of element sequences with the surrounding intron produced wild-type transcripts that presumably were responsible for the observed residual gene expression in the endosperm. In this study, we report that one of these alleles, wxG, has a tissue-specific phenotype with 30-fold more WX enzymatic activity in pollen than in the endosperm. Quantification of wxG-encoded transcripts in pollen and the endosperm demonstrates that this difference can be accounted for by tissue-specific differences in RNA processing. Specifically, there is approximately 30-fold more correctly spliced RNA in pollen than in the endosperm. Based on an analogy to similar examples of tissue-specific alternative splicing in animal systems, we hypothesize that the tissue-specific phenotype of the wxG allele may reflect differences in the concentration of splicing factors in these tissues.